PENGARUH EFIKASI DIRI DAN STATUS SOSIAL EKONOMI ORANG TUA TERHADAP MINAT BERWIRAUSAHA SMK SUKAWATI GEMOLONG - Pratiwi Nur Laily (JIKAP (Jurnal Informasi dan Komunikasi Administrasi Perkantoran), 2019)
The purpose of this research were to find out 1) the effects of self-effficacy toward student’s interest in entrepreneurship program office administration SMK Sukawati Gemolong, 2) the effects of social economics status of the parents toward student’s interest in entrepreneurship program office administration SMK Sukawati Gemolong, and 3) the effects of self-efficacy and social economics status of the parents together toward student’s interest in entrepreneurship program office administration SMK Sukawati Gemolong.This research used a descriptive metods with quantitative. The population in this research were all student of class XI and XII program office administration SMK Sukawati Gemolong which amounted to 79 students. The sample in this research amount to 66 students, taken with stratified proportional random sampling. Data collection techniques using questionnaire and document. The data analysis technique using multiple regression, t test, and F test. The conclusions of this research is that there are positive and significant  effect of 1) self-effficacy toward student’s interest in entrepreneurship program office administration SMK Sukawati Gemolong with tcount  amount 8,079 (α = 5%, 2) social economics status of the parents toward student’s interest in entrepreneurship program office administration SMK Sukawati Gemolong with tcount  amount 3,029 (α = 5%), and 3) self-efficacy and social economics status of the parents together toward student’s interest in entrepreneurship program office administration SMK Sukawati Gemolong fcount amount 45,412 (α = 5%). The variable of self-efficacy gives relative contribution amount 82,78%  and effective contibution amount 48,84%. The variable of social economics satus of the parents gives relative contribution amount 17,36% and effective contibution amount 10,24%.